Enhancing prime editor activity by directed protein evolution in yeast - Weber, Yanik; Böck, Desirée; Ivașcu, Anastasia; Mathis, Nicolas; Rothgangl, Tanja; Ioannidi, Eleonora I.; Blaudt, Alex C.; Tidecks, Lisa; Vadovics, Máté; Muramatsu, Hiromi; Reichmuth, Andreas; Marquart, Kim F.; et al. (Nature communications, 2024)
Prime editing is a highly versatile genome editing technology that enables the introduction of base substitutions, insertions, and deletions. However, compared to traditional Cas9 nucleases prime editors (PEs) are less active. In this study we use OrthoRep, a yeast-based platform for directed protein evolution, to enhance the editing efficiency of PEs. After several rounds of evolution with increased selection pressure, we identify multiple mutations that have a positive effect on PE activity in yeast cells and in biochemical assays. Combining the two most effective mutations – the A259D amino acid substitution in nCas9 and the K445T substitution in M-MLV RT – results in the variant PE_Y18. Delivery of PE_Y18, encoded on DNA, mRNA or as a ribonucleoprotein complex into mammalian cell lines increases editing rates up to 3.5-fold compared to PEmax. In addition, PE_Y18 supports higher prime editing rates when delivered in vivo into the liver or brain. Our study demonstrates proof-of-concept for the application of OrthoRep to optimize genome editing tools in eukaryotic cells. Compared to traditional Cas9 nucleases prime editors (PEs) are less active. Here the authors use OrthoRep, a yeast-based platform for directed protein evolution to enhance the editing efficiency of PEs: they identify mutations that have a positive effect on kinetics and use this knowledge to generate an efficient in vivo PE.